Sequence, structure and pathology of the fully annotated terminal 2 Mb of the short arm of human chromosome 16. - Daniels, R; Peden, J; Lloyd, C; Horsley, S; Clark, K; Tufarelli, C; Kearney, L; Buckle, V; Doggett, N; Flint, J; Higgs, D (2001)
We have sequenced 1949 kb from the terminal Giemsa light band of human chromosome 16p, enabling us to fully annotate the region extending from the telomeric repeats to the previously published tuberous sclerosis disease 2 (TSC2) and polycystic kidney disease 1 (PKD1) genes. This region can be subdivided into two GC-rich, Alu-rich domains and one GC-rich, Alu-poor domain. The entire region is extremely gene rich, containing 100 confirmed genes and 20 predicted genes. Many of the genes encode widely expressed proteins orchestrating basic cellular processes (e.g. DNA recombination, repair, transcription, RNA processing, signal transduction, intracellular signalling and mRNA translation). Others, such as the alpha globin genes (HBA1 and HBA2), PDIP and BAIAP3, are specialized tissue-restricted genes. Some of the genes have been previously implicated in the pathophysiology of important human genetic diseases (e.g. asthma, cataracts and the ATR-16 syndrome). Others are known disease genes for alpha thalassaemia, adult polycystic kidney disease and tuberous sclerosis. There is also linkage evidence for bipolar affective disorder, epilepsy and autism in this region. Sixty-three chromosomal deletions reported here and elsewhere allow us to interpret the results of removing progressively larger numbers of genes from this well defined human telomeric region.